2018
DOI: 10.1038/s41467-018-03549-6
|View full text |Cite
|
Sign up to set email alerts
|

Operando tribochemical formation of onion-like-carbon leads to macroscale superlubricity

Abstract: Stress-induced reactions at the sliding interface during relative movement are known to cause structural or chemical modifications in contacting materials. The nature of these modifications at the atomic level and formation of byproducts in an oil-free environment, however, remain poorly understood and pose uncertainties in predicting the tribological performance of the complete tribosystem. Here, we demonstrate that tribochemical reactions occur even in dry conditions when hydrogenated diamond-like carbon (H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(117 citation statements)
references
References 38 publications
4
107
0
1
Order By: Relevance
“…The scope of the review is limited to simulations with empirical potentials (i.e., ab initio calculations are not included) that capture the formation and breaking of chemical bonds driven by shear force. The review excludes studies that do not consider sliding, although reactive molecular dynamics simulations have been used to model tribologically relevant reactions driven thermally and/or via normal force (see, for example, [51][52][53][54][55][56]). Furthermore, although the empirical model used for each study discussed in this review is mentioned, the different potentials are not compared.…”
Section: Introductionmentioning
confidence: 99%
“…The scope of the review is limited to simulations with empirical potentials (i.e., ab initio calculations are not included) that capture the formation and breaking of chemical bonds driven by shear force. The review excludes studies that do not consider sliding, although reactive molecular dynamics simulations have been used to model tribologically relevant reactions driven thermally and/or via normal force (see, for example, [51][52][53][54][55][56]). Furthermore, although the empirical model used for each study discussed in this review is mentioned, the different potentials are not compared.…”
Section: Introductionmentioning
confidence: 99%
“…Detonation nanodiamonds (DNDs) have attracted great attention in the scientific and industrial communities in the past decade [1,2]. Today, DNDs are already evaluated in applications from composite materials in dental implants [3] and drug delivery applications [4] to diamond growth [5] and lubrication [6]. At the same time, many questions about their exact nanoscale composition, crystal structure, and surface properties remain unanswered, necessitating continued efforts in the detailed material characterization of DNDs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an architecture of onion‐like carbon obtained from the tribochemical reaction of a hydrogenated DLC surface sliding against MoS 2 nanolayers with nanodiamonds was found to show macroscale superlubricity at the dry nitrogen condition . Detailed MD simulation ( Figure a–h) and experimental (Figure i–l) investigations indicated that under high contact stress, sulfur atoms diffusing from dissociated MoS 2 resulted in amorphization of nanodiamonds, and consequently caused the transformation to the onion‐like carbon‐based structure.…”
Section: D Nanomaterialsmentioning
confidence: 99%
“…The frictional performance of materials, particularly their superlubricity behavior in which friction completely or nearly vanishes, have received increasing interest . Superlubricity with a state of friction coefficient below 0.001, first proposed by Hirano and Shinjo, has been considered to be one of the most effective ways to alleviate the negative effects of friction and wear.…”
Section: Introductionmentioning
confidence: 99%